Applicable law, jurisdiction, and recognition of decisions in matters relating to property regimes of spouses and partners in European and Italian private international law. Issue 1 (20th November 2018) - Damascelli, Domenico
Abstract: After describing the framework of the European Union's law sources on family matters, this article addresses the private international law (applicable law, jurisdiction, and recognition of decisions) discipline of property regimes between spouses and between partners of a registered partnership, at the outset, in view of the new (EU) Regulation Nos 2016/1103 and 2016/1104 and, secondarily, in view of the Italian conflict of law system (Law No 218/1995).